Glasovanje osoba s intelektualnim teškoćama u kontekstu temeljnih ljudskih vrijednosti - Gvozdanović Debeljak, Aleksandra (Array, 2018)
The aim of the paper is to show the level of awareness of people with intellectual disabilities on political elections and to describe the reasons, ways and expectations for which persons with intellectual disabilities do (not) vote. The sample is a heterogeneous group of ten persons with intellectual disabilities from the Inclusion Centre Osijek aged from 28 to 65. Interview (semi-structured interview) has been used as a research method. The interviews took place on the Centre’s premises. The participants responded to three basic questions, as well as to sub-questions asked by the interviewers. Research data have been shown at a qualitative level. The interview results point to inadequate awareness of the respondents on political elections, resulting in the lack of awareness of the respondents on the purpose of political elections and the functionality of voting participation. Also, the voter turnout is low and, consequently, there is an inadequate use of their voting rights in terms of political participation as disabled persons. Realization of rights of persons with disabilities must not depend on the (non)readiness of the system or the will of individuals but must be the primary goal of inclusive policy and society in general.